STRATEGI OPTIMASI DIGITAL MARKETING UNTUK MENINGKATKAN PENJUALAN ONLINE (STUDI KASUS TRAVEL HAJI DAN UMRAH SINAI BUKITTINGGI - Widia Sari; Indika Juang Putra (CV. ADIBA AISHA AMIRA, 2025)
This study examines the digital marketing optimization method used by Sinai Bukittinggi Hajj and Umrah Travel to boost online sales. Although social media has been used for advertising, prospective pilgrims are still hesitant to register online due to the lack of comprehensive information in the content. This study uses a descriptive qualitative methodology, with data collection through documentation, interviews, and observations. Data reduction, data presentation, and drawing conclusions are the steps involved in data analysis. The findings of this study indicate that the effectiveness of digital marketing is still constrained by the lack of information in the content, low trust in online registration, and limited team skills in content creation. Supporting factors for this strategy include the wide reach of social media and Islamic content policies, while inhibiting factors are limited information and lack of marketing team skills. Optimization of digital marketing needs to be done by improving content quality, increasing the trust of prospective pilgrims, and training the digital marketing team.